2010
DOI: 10.1021/ar900275b
|View full text |Cite
|
Sign up to set email alerts
|

New Photovoltaic Devices Based on the Sensitization of p-type Semiconductors: Challenges and Opportunities

Abstract: Because solar energy is the most abundant renewable energy resource, the clear connection between human activity and global warming has strengthened the interest in photovoltaic science. Dye-sensitized solar cells (DSSCs) provide a promising low-cost technology for harnessing this energy source. Until recently, much of the research surrounding DSSCs had been focused on the sensitization of n-type semiconductors, such as titanium dioxide (Gratzel cells). In an n-type dye-sensitized solar cell (n-DSSC), an elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
392
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(397 citation statements)
references
References 49 publications
(103 reference statements)
5
392
0
Order By: Relevance
“…Among them, nickel oxide, a p-type transparent semiconductor, has been one of the most investigated members. [135][136][137] In the class of metal oxides, A 2 BO 4 spinels are certainly important members. It has been recently demonstrated by Paudel et al that neither oxygen vacancies nor cation vacancies can be the leading source of conductive behaviour in spinels.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, nickel oxide, a p-type transparent semiconductor, has been one of the most investigated members. [135][136][137] In the class of metal oxides, A 2 BO 4 spinels are certainly important members. It has been recently demonstrated by Paudel et al that neither oxygen vacancies nor cation vacancies can be the leading source of conductive behaviour in spinels.…”
Section: Discussionmentioning
confidence: 99%
“…5 Because of this interesting combination of electrical and optical properties, NiO x has been considered for energy storage applications, [6][7][8] in electrochromic devices as transparent electrode, 9-17 in optoelectronic devices as electron barrier, 18,19 for gas sensing, 20,21 and, more recently, in dye-sensitized solar cells (DSCs) as photoactive cathode. [22][23][24][25][26][27][28][29][30][31][32][33][34][35] The utilization of NiO x in such diverse applications has been accompanied by the development of various preparation methods and deposition techniques, aimed at producing NiO x -based materials with variable chemical composition, electrical resistivity, compactness and morphology. Examples include electrochemical deposition, 36 chemical vapor 37 and bath deposition, 38 spray pyrolysis, 39,40 sol-gel method, 14,23,25,41 hydrothermal synthesis, 29,42 and sputtering.…”
Section: Introductionmentioning
confidence: 99%
“…The working principle is very similar to an n-type DSC, the difference being that the excited state of the sensitizer is now reductively quenched by the semiconductor, which is the sensitizer excited state injects holes into the valence band of the p-type semiconductor [25][26][27]. While the general design of dyes consists of electron-donor (D) and electron-acceptor (A) linked with π conjugation (D-π-A), the main difference between n-type dye and p-type dye is position of the acceptor: the anchoring group is attached on the electron-acceptor part for n-type dyes while the group is attached on the electron-donor part for p-type dyes.…”
Section: M`eṕ Injectedq ñ M´(6)mentioning
confidence: 99%
“…Since He et al first demonstrated the generation of a cathodic photocurrent from organic dye sensitized nanostructured NiO cathode [68], many sophisticatedly designed dyes have been reported (details about their molecular structures can be found in [26]). Among them, a donor-acceptor type dye, comprising a perylene monoimide (PMI) as the acceptor and an oligothiophene coupled to triphenylamine as the donor holds the record efficiency of 0.41% [27].…”
Section: Niomentioning
confidence: 99%